Inovasi Pembelajaran Akidah Akhlak dalam Perspektif Filsafat Islam Studi Analisis Ontologi, Epistemologi, dan Aksiologi di SDIT Sahabat Gondangrejo Karanganyar - Mujiburrahman, Mujiburrahman; MasrurohMasruroh, Masruroh (TSAQOFAH, 2026)
Learning in Akidah Akhlak plays a strategic role in shaping students’ religious and moral character from an early age; however, the challenges of the digital era demand instructional innovations that are not only pedagogically effective but also philosophically robust. This study aimed to analyze learning innovations in Akidah Akhlak at SDIT Sahabat Gondangrejo Karanganyar from the perspective of Islamic philosophy by examining the ontological, epistemological, and axiological dimensions. A qualitative approach with a case study method was employed, with data collected through classroom observations, interviews with the principal and teachers, and document analysis. The findings show that, ontologically, Akidah Akhlak learning is understood as a process of instilling faith and moral values derived from divine revelation and human fitrah; epistemologically, instructional innovation integrates naqli and ‘aqli sources of knowledge through active and collaborative methods and the use of technology-based media; and axiologically, learning is oriented toward the formation of Islamic character, the strengthening of moral values, and the implementation of noble conduct in students’ daily lives. This study contributes to reinforcing the philosophical foundations of innovation in Akidah Akhlak instruction and offers recommendations for developing Islamic Religious Education that is more relevant to the context of contemporary Islamic elementary education.